Analisis Pengadaan Obat Menggunakan Metode Konsumsi di Bagian Logistik Farmasi Rumah Sakit Nur Hidayah Bantul - Novia Indras Wari; Mudayana, Ahmad Ahid (International Journal of Healthcare Research, 2022)
The consumption method is a method carried out by evaluating past drug use as a basis for determining the estimated need, then adjusting it to the strategic plan of the hospital and hospital pharmacy, so that the final result is a list of drug needs. This study aims to analyze the need for pharmaceutical logistics using the consumption method at Nur Hidayah Hospital, Bantul. The type of research used in this research is qualitative research and the research subjects are 4 people. Data collection techniques in this study using interviews and observation. Test the validity and credibility of the data in this study using source triangulation and technique triangulation. Data analysis used analysis method from milles and Huberman. Based on the results of this study indicate that 1) the largest average use is Metformin 500 mg as many as 6,695 tablets, 3) Lead time is adjusted to the PBF and assessed by score. 4) The amount of safety stock is proportional to the average amount of usage per month. 5) The results of calculating the total number of drug needs for the 2022 period with the consumption method of the five types of drugs have more drug needs than the stock in storage so they need to be added to meet the needs. Based on the results of research that has been done, this combination method is less efficient if used in the Pharmacy Installation of Nur Hidayah Hospital.